2017
DOI: 10.1155/2017/7507523
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Properties of Amylolytic Enzymes Produced by Gongronella butleri Using Agroindustrial Residues on Solid-State Fermentation

Abstract: Amylases catalyze the hydrolysis of starch, a vegetable polysaccharide abundant in nature. These enzymes can be utilized in the production of syrups, alcohol, detergent, pharmaceutical products, and animal feed formulations. The aim of this study was to optimize the production of amylases by the filamentous fungus Gongronella butleri by solid-state fermentation and to evaluate the catalytic properties of the obtained enzymatic extract. The highest amylase production, 63.25 U g−1 (or 6.32 U mL−1), was obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Thus, temperature contributes to the factor responsible for the secretion of amylase. Cavalheiro et al documented that high enzymatic activity for amylase production by Gongronella butleri was between pH ranges of 4.0-5.5 [99]. Nwagu and Okolo reported that amylase produced by A. fumigatus maintained 94% of its activity at pH 4.5-6.5 for 24 hours [99].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, temperature contributes to the factor responsible for the secretion of amylase. Cavalheiro et al documented that high enzymatic activity for amylase production by Gongronella butleri was between pH ranges of 4.0-5.5 [99]. Nwagu and Okolo reported that amylase produced by A. fumigatus maintained 94% of its activity at pH 4.5-6.5 for 24 hours [99].…”
Section: Discussionmentioning
confidence: 99%
“…Cavalheiro et al documented that high enzymatic activity for amylase production by Gongronella butleri was between pH ranges of 4.0-5.5 [99]. Nwagu and Okolo reported that amylase produced by A. fumigatus maintained 94% of its activity at pH 4.5-6.5 for 24 hours [99]. de-Souza and Magalhães reported that A. niger has important hydrolytic capacities in amylase production and its tolerance of acidity (pH<3) could be a factor in the production of amylase by different Aspergillus spp isolated [100].…”
Section: Discussionmentioning
confidence: 99%
“…Our research group has been working on the description of new biocatalysts from enzymeproducing filamentous fungi isolated from the Midwest region of Brazil, with appreciable biotechnological characteristics such as low production cost, high structural stability, and broad industrial applicability (Cavalheiro et al 2017, Costa et al 2019, Garcia et al 2015, Morais et al 2018). Among the strains recently isolated by our team, the thermophilic filamentous fungus Thermoascus crustaceus stood out for the production of the enzyme β-glucosidase.…”
Section: Introductionmentioning
confidence: 99%